Increasing Student Satisfaction: The Role of Charismatic Leadership of Lecturers and the Technology Used - Subarto; Solihin, Dede (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The application of appropriate technology-based learning media needs to be applied in the context of online learning in the current 5.0 era. The media used must be adjusted to the psychological conditions of students. The purpose of this study was to identify the charismatic leadership of lecturers and the use of technology that enables student involvement and ultimately improves student learning achievement and satisfaction. This type of research is quantitative research. The data collection method uses a questionnaire. The sample used was 220 students while the data analysis method used a structural equation model based on Variance. The results of this study indicate that the charismatic leadership of lecturers has a significant effect on student cognitive involvement, student emotional involvement and student behavioral involvement. The variable of technology utilization each has a significant effect on Student Cognitive Engagement and Student Emotional Engagement but does not have a significant effect on Student Behavioral Engagement. Then Student Cognitive Engagement, Student Emotional Engagement and Student Behavioral Engagement have a significant effect on Student Learning Achievement and Student Satisfaction. The findings of this study emphasize the importance of lecturer and student characteristics for effective interaction and results in online learning.